A Major Locus for Manganese Tolerance Maps on Chromosome A09 in a Doubled Haploid Population of Brassica napus L. - Raman, Harsh; Raman, Rosy; McVittie, Brett; Orchard, Beverley; Qiu, Yu; Delourme, Regine (Frontiers in Plant Science, 2017)
Soil acidity poses a major threat to productivity of several crops; mainly due to the prevalence of toxic levels of Al3+ and Mn2+. Crop productivity could be harnessed on acid soils via the development of plant varieties tolerant to phytotoxic levels of these cations. In this study, we investigated the extent of natural variation for Mn2+ tolerance among ten parental lines of the Australian and International canola mapping populations. Response to Mn2+ toxicity was measured on the bases of cotyledon chlorosis, shoot biomass and leaf area in nutrient solution under control (9 µM of MnCl2˙4H2O) and Mn treatment (125 µM of MnCl2˙4H2O). Among parental lines, we selected Darmor-bzh and Yudal that showed significant and contrasting variation in Mn2+ tolerance to understand genetic control and identify the quantitative trait loci (QTL) underlying Mn2+ tolerance. We evaluated parental lines and their doubled haploid (DH) progenies (196 lines) derived from an F1 cross, Darmor-bzh/Yudal for Mn2+ tolerance. Mn2+-tolerant genotypes had significantly higher shoot biomass and leaf area compared to Mn2+-sensitive genotypes. A genetic linkage map based on 7,805 DArTseq markers corresponding to 2,094 unique loci was constructed using DArTseq markers and further utilised for QTL identification. A major locus, BnMn2+.A09 was mapped with a SNP marker, Bn-A09-p29012402 (LOD score of 34.6) accounting for most of the variation in Mn2+ tolerance on chromosome A09. This is the first report on the genomic localisation of a Mn2+ tolerance locus in B. napus. Additionally, an orthologue of A. thaliana encoding for cation efflux facilitator transporter was located within 3,991 bp from significant SNP marker associated with BnMn2+.A09. A suite of genome sequence based markers (DArTseq and Illumina Infinium SNPs) flanking the BnMn2+.A09 locus would provide an invaluable tool for various molecular breeding applications to improve canola production and profitability on Mn2+ toxic soils.